3D Interdigitated Microsupercapacitors with Record Areal Cell Capacitance. Issue 27 (16th May 2019) - Ferris, Anaïs; Bourrier, David; Garbarino, Sébastien; Guay, Daniel; Pech, David
Abstract: Due to their high‐power density and long lifetime, microsupercapacitors have been considered as an efficient energy supply/storage solution for the operation of small electronic devices. However, their fabrication remains confined to 2D thin‐film microdevices with limited areal energy. In this study, the integration of all‐solid‐state 3D interdigitated microsupercapacitors on 4 in. silicon wafers with record energy density is demonstrated. The device electrodes are composed of a pseudocapacitive hydrated ruthenium dioxide RuO2 deposited onto highly porous current collectors. The encapsulated devices exhibit cell capacitance of 812 mF cm −2 per footprint area at an energy density of 329 mJ cm −2, which is the highest value ever reported for planar configuration. These components achieve one of the highest surface energy/power density trade‐offs and address the issue of electrical energy storage of modern electronics. Abstract : The successful integration of 3D pseudocapacitive electrodes on a silicon wafer to realize all‐solid‐state interdigitated microsupercapacitors outperforming the state of the art is reported. This work constitutes a major step forward toward developing microscale energy storage for embedded microsystems where energy autonomy is one of the factors limiting further progress.